2015
DOI: 10.1371/journal.pone.0145057
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Augmentation of Cupriavidus sp. CY-1 into 2,4-D Contaminated Soil: Microbial Community Analysis by Culture Dependent and Independent Techniques

Abstract: In the present study, a 2,4-dichlorophenoxyacetic acid (2,4-D) degrading bacterial strain CY-1 was isolated from the forest soil. Based on physiological, biochemical and 16S rRNA gene sequence analysis it was identified as Cupriavidus sp. CY-1. Further 2,4-D degradation experiments at different concentrations (200 to 800 mg l-1) were carried out using CY-1. Effect of NaCl and KNO3 on 2,4-D degradation was also evaluated. Degradation of 2,4-D and the metabolites produced during degradation process were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…3 of the Ribosomal Database Project-RDP (Cole et al 2005). Thus, a phylogenetic tree was designed using 21 CdtB isolated in this study and eight referential strains found in the NCBI nucleotides database, reported previously as cadmium-tolerant bacteria (Ferianc and Farewell 1998;Chen et al 2008;Ma et al 2012;Schwager et al 2012;Chien et al 2014;Chang et al 2015). A phylogenetic analysis was performed using MEGA7 software.…”
Section: Discussionmentioning
confidence: 99%
“…3 of the Ribosomal Database Project-RDP (Cole et al 2005). Thus, a phylogenetic tree was designed using 21 CdtB isolated in this study and eight referential strains found in the NCBI nucleotides database, reported previously as cadmium-tolerant bacteria (Ferianc and Farewell 1998;Chen et al 2008;Ma et al 2012;Schwager et al 2012;Chien et al 2014;Chang et al 2015). A phylogenetic analysis was performed using MEGA7 software.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences were compared with those deposited in the GenBank nucleotide database using the BLAST program. These sequences were further aligned with the closest matches found in the GenBank database with the CLUSTALW function of Molecular Evolutionary Genetics Analysis package (MEGA) [20]. Neighbor-joining phylogenetic tree was constructed with the MEGA version 6.0.…”
Section: Bacillus Sp Cyr2 Isolationmentioning
confidence: 99%
“…Our results are consistent with several studies showing that the 2,4-D herbicide treatment, used at the recommended agricultural dose, has little or no impact on bacterial communities (Bouseba et al, 2009;Zabaloy et al, 2010;Inoue et al, 2012) and that the inoculation of a 2,4-D degrading-Cupriavidus sp. strain did not disturb the soil indigenous microorganisms (Chang et al, 2015).…”
Section: Abundance Of 24-d Bacterial Degradersmentioning
confidence: 92%
“…Hence its frequent use as a molecular marker for the degradation potential of 2,4-D in the environment (Stibal et al, 2012;Mierzejewska et al, 2019). Curative 2,4-D bioaugmentation assays, using between 10 5 to 10 8 CFU/g -1 soil of various degrading-strains, were carried out in soil slurry (Inoue et al, 2012;Chang et al, 2015), in reactor (Pepper et al, 2002), in sieved or amended soil microcosms (Dejonghe et al, 2000;Xia et al, 2017) or more recently in combination with other mitigation strategies (Yang et al, 2018;Barba et al, 2021). The removal of 2,4-D has also been investigated in soil microcosms following simultaneous application of the herbicide and its degrading-strain (Önneby et al, 2010).…”
Section: Introductionmentioning
confidence: 99%